Prioritization Product Portfolio Selection Framework Using Aanalytical Hierarchy Process: A Case of Information Communication Technology Company - Dhedy Pamardi, Irmawan; Dwi Lestari, Yuliani (The Indonesian Journal of Business Administration, 2017)
Abstract – Indonesia has total population of 255.500.000 persons in 2015, followed by 430% growing rate of internet user populations for the last five years, and it became the second fastest growing internet user populations in the world. Indonesian Government IT spending also expected to increase and continue to account around 25% of the IT market. This condition could be a potential market for the Information, Communication, and Technology industries. Due to the information confidentiality, the subject of this research would refers to PT. ABC as the subject of research. PT ABC, is one of the state-owned company that fully owned by the Indonesian Government. While according to the gap analysis shown that since fiscal year 2012 to 2015 the company suffered from negative revenue growth. According to the Root Cause Analysis process using Current Reality Tree techniques, the identifiable root cause of the current business issues is started from poor planning of product line portfolio selection.  The tools that would be used for the assessment process for this research is Analytical Hierarchy Process. Fundamentally, the Analytical Hierarchy Process methods works by developing priorities for alternatives and the criteria used to judge the alternatives. Priority assessment using Analytical Hierarchy Process with BOCR control criteria has been conducted to prioritized product portfolio selection, it suggest that the characteristics of managerial in PT ABC would prefer Benefits 52,34%; Costs 26,67%; Opportunities 14,60%; and Risks 6,39% respectively. In accordance to those managerial characteristics, it suggest that the Management in PT ABC should consider to prioritized on Product Line A 49,83%, Product Line B 28,74%, and Product Line C 21,43% respectively. Keywords: Analytical Hierarchy Process, BOCR, Current Reality Tree, ICT Industries, Negative Revenue Growth, Strategic Busines Units, TOWS Analysis.